The complete mitochondrial genome of cutlassfish (Trichiurus japonicus) from South China Sea - Lei Xu; Xuehui Wang; Feiyan Du (Mitochondrial DNA. Part B. Resources, 2019)
Trichiurus japonicus is one of Trichiuridae and widely distributed in the North Pacific Ocean. In this study, we described the complete mitochondrial genome of Trichiurus japonicus. The genome is 16797 bp in length, encoding the standard set of 13 protein-coding genes, 21 transfer RNA genes, two ribosomal RNA genes, and a non-coding D-loop, with circular organization. The overall base composition of the whole mitochondrial genome was A (28.7%), T (25.83%), G (16.2%), and C (29.27%) with an AT bias of 54.53%. The longest protein-coding gene of these species was ND5, whereas the shortest ATP8.